2008
DOI: 10.1002/pbc.21453
|View full text |Cite
|
Sign up to set email alerts
|

Congenital amegakaryocytic thrombocytopenia: The diagnostic importance of combining pathology with molecular genetics

Abstract: Congenital Amegakaryocytic Thrombocytopenia (CAMT) is a rare bone marrow failure syndrome that presents with isolated thrombocytopenia within the first year of life. Classic diagnostic bone marrow findings reveal absent or significantly decreased megakaryocytes with otherwise normal marrow cellularity. We present a newborn with thrombocytopenia whose initial bone marrow aspirate showed an appropriate number of megakaryocytes. CAMT was subsequently diagnosed after molecular testing demonstrated a mutation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…NAIT is more common than CAMT (1 : 1000-1 : 2000 live births [7,8] compared with less than 100 reported cases of CAMT). In a child suspected to have NAIT, if thrombocytopenia does not resolve after 3 months, alternative diagnoses such as CAMT should be explored [9]. NAIT was not considered because of the ongoing thrombocytopenia after 6 months in our patient.…”
Section: Discussionmentioning
confidence: 78%
“…NAIT is more common than CAMT (1 : 1000-1 : 2000 live births [7,8] compared with less than 100 reported cases of CAMT). In a child suspected to have NAIT, if thrombocytopenia does not resolve after 3 months, alternative diagnoses such as CAMT should be explored [9]. NAIT was not considered because of the ongoing thrombocytopenia after 6 months in our patient.…”
Section: Discussionmentioning
confidence: 78%
“…9 The c-Mpl P106L show constitutive activity that can be further stimulated by THPO The P106L mutation affects an extracellular domain of the c-Mpl receptor, which is a hotspot for both gain-of-function and loss-offunction mutations. 9,[25][26][27][28] Thus, this domain appears to be of critical physiological importance, which led us to perform detailed functional studies of the P106L gain-of-function and of mutations that have been reported to cause loss of receptor function but are located in close proximity. [25][26][27][28] To this end, we designed c-Mpl constructs coding for the WT receptor, the loss-of-function mutations R102P and F104S, and the P106L gain-of-function mutation, and we stably expressed these genes in cytokine-dependent Ba/F3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] THPO binding to CRM1 has been shown to initiate signal transduction. 29,30 Deletion of this critical domain activates c-Mpl, suggesting an inhibitory function that can be relieved by ligand binding.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow evaluation in newborns with CAMT typically demonstrates normal overall cellularity with an isolated reduction or absence of megakaryocytes 1, although in some cases marrows studied early in the course of the disease can have misleadingly minimal findings and serial marrows may be required to clarify the diagnosis (Fox et al, submitted and 2). Although originally a clinical diagnosis, CAMT can now be molecularly defined by mutations involving the TPO receptor c-Mpl 3, 4.…”
Section: Camt: Presentation and Differential Diagnosismentioning
confidence: 99%